Efek Pemberian Pupuk Hayati VP3 yang Diperkaya Trichoderma viride FRP3 terhadap Pertumbuhan Fase Generatif Tanaman Kedelai (Glycine max L.) - erwin erwinn; Anis Rosyidah; Novi Arfarita (AGRONISMA, 2022)
VP3 biofertilizer is a fertilizer composed of vermiwash, molasses and 1% PEG, with 3 bacterial isolates added. Trichoderma viride FRP3 is a bioremediation agent that can degrade land contaminated with the herbicide glyphosphate. The purpose of this study was to determine the effect of the application of VP3 biofertilizer enriched with Trichoderma viride FRP3 on the growth of the generative phase of soybean (Glycine max L.) grown in greenhouses. The research was conducted in the greenhouse of the Faculty of Agriculture, and Laboratory of Microbiology, University of Islam Malang from November 2021 to February 2022. The research design used a Simple Randomized Block Design (RBD) with 7 treatments and was repeated 3 times. The results of the study showed that treatment N (NPK fertilizer) gave the highest average yield on observations of plant height, number of leaves, leaf area, total flowers, and total pods. The best result on the parameter of the percentage of flowers into pods was in treatment V2 (compost fertilizer + manure + VP3 biofertilizer 3 times application) which was 31,74%.Â Keywords : VP3 Biofertilizer, Trichoderma viride FRP3, Soybean.